Fiscal Decentralization and Human Poverty in Nepal: A Causal Analysis - Khanal, Gopi K. (Journal of Management and Development Studies, 2018)
This paper examines the contribution of fiscal decentralization on reducing human poverty in the districts of Nepal. Development landscape of twenty-first century has changed with more focus on human-centric development under the umbrella of human development. Accordingly, the broader goal of development is not only to increase the economic growth but also to enlarge the choices of people. The key finding of this paper is that the ongoing efforts on fiscal decentralization are supportive to reduce the human poverty in the districts. However, fiscal decentralization does not support to improve every dimension of human development. The paper also finds that urbanization is good for reducing human poverty.